The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21608/jbaar.2016.106941
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of ginger extract against pathological alterations induced in mice bearing solid tumors.

Abstract: This study was prepared to explore the effect of ginger extract in defeating the Ehrlich Ascites Carcinoma (EAC) injected subcutaneously in mice and induced solid tumour. After the solid tumour formation; the mice were classified into four groups (control, tumour untreated, ginger and ginger & tumour). Eight mice were grouped separately in each cage. Mice were killed and dissected at the end of this investigation; liver and kidney were removed for histopathological study. The biochemical parameters (ALT, AST, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Besides that, the decline in the level of albumin produced by the liver’s hepatocytes in EST–bearing mice, valuable markers for liver function, refers to the harmful effect of EAC that causes the decrease in the biosynthetic capacity of the liver to synthesize plasma protein. Also, EAC proliferation induced renal tissue injury and raised kidney function . Our results are matched with a recent study .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides that, the decline in the level of albumin produced by the liver’s hepatocytes in EST–bearing mice, valuable markers for liver function, refers to the harmful effect of EAC that causes the decrease in the biosynthetic capacity of the liver to synthesize plasma protein. Also, EAC proliferation induced renal tissue injury and raised kidney function . Our results are matched with a recent study .…”
Section: Discussionsupporting
confidence: 91%
“…Also, EAC proliferation induced renal tissue injury and raised kidney function. 67 Our results are matched with a recent study. 68 The changes in liver and kidney functions could be due to the generation of ROS that induces tissue damage by destroying cellular homeostasis.…”
Section: Discussionsupporting
confidence: 90%
“…Hepatic toxicity induced through tumor growth may be due to the extreme production of ROS that leads to oxidative stress and damage [ 46 , 64 , 65 ]. The present data indicated that treatment with APAN improved liver biomarkers, and when ETO was used, improvement also occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Badawy et al [66] indicated that ginger extract (200 mg/kg) ameliorates the histopathological and ultrastructure changes in the hepatocytes of the fetuses maternally injected with the antiepileptic drug gabapentin. Also, Badr et al [67] showed that ginger extracts at a dose of 120 mg/kg caused some ameliorations in the liver structure after solid tumor formation in mice. Gholampour et al [68] reported that ginger hydroalcoholic extract exerts a protective effect against ferrous sulfate-induced pathological changes in both rat liver and kidney.…”
Section: Discussionmentioning
confidence: 99%